Neurochemical Architecture of the Central Complex Related to Its Function in the Control of Grasshopper Acoustic Communication - Kunst, Michael; Pförtner, Ramona; Aschenbrenner, Katja; Heinrich, Ralf (PloS one, 2011)
The central complex selects and coordinates the species- and situation-specific song production in acoustically communicating grasshoppers. Control of sound production is mediated by several neurotransmitters and modulators, their receptors and intracellular signaling pathways. It has previously been shown that muscarinic cholinergic excitation in the central complex promotes sound production whereas both GABA and nitric oxide/cyclic GMP signaling suppress its performance. The present immunocytochemical and pharmacological study investigates the question whether GABA and nitric oxide mediate inhibition of sound production independently. Muscarinic ACh receptors are expressed by columnar output neurons of the central complex that innervate the lower division of the central body and terminate in the lateral accessory lobes. GABAergic tangential neurons that innervate the lower division of the central body arborize in close proximity of columnar neurons and thus may directly inhibit these central complex output neurons. A subset of these GABAergic tangential neurons accumulates cyclic GMP following the release of nitric oxide from neurites in the upper division of the central body. While sound production stimulated by muscarine injection into the central complex is suppressed by co-application of sodium nitroprusside, picrotoxin-stimulated singing was not affected by co-application of this nitric oxide donor, indicating that nitric oxide mediated inhibition requires functional GABA signaling. Hence, grasshopper sound production is controlled by processing of information in the lower division of the central body which is subject to modulation by nitric oxide released from neurons in the upper division.